ROLE OF ANIMAL BEHAVIOUR AND WELFARE IN LIVESTOCK PRODUCTION AND MANAGEMENT - SAEED, HA; HAIDER, MJ; ANSARI, TS; FATIMA, A; KHALID, A; Gilani, MA; SALEEM, M; SHOAIB, M; SARMAD, M; AHMAR, M; SAKHAWAT, A (Biological and Clinical Sciences Research Journal, 2023)
Animal behavior and welfare play pivotal roles in livestock production and management, shaping the well-being of animals and the industry’s overall success. The primary aim of the study is to find the role of animal behaviour and welfare in livestock production and management. The comprehensive study was conducted at University of Veterinary & Animal Sciences Lahore from November 2021 to January 2022. Behavioral data were collected from various livestock species, including cattle, poultry, pigs, and sheep. Observations were made in various settings, such as farms, feedlots, and poultry houses, to capture a comprehensive view of animal behavior. A total of 220 animals were included in the research. Observations revealed that cattle exhibited grazing behaviors for an average of 6 hours daily, while poultry engaged in frequent feeding bouts totaling 10 hours daily. Pigs and sheep displayed flexible feeding behaviors with an average of 8 hours per day, consistent with earlier findings. It is concluded that this study plays a pivotal role in animal behavior and welfare in livestock production and management. Understanding and accommodating natural behaviors, mitigating environmental stressors, and adhering to ethical guidelines contribute to healthier, more contented livestock.